Low Dose of Nanocapsules Containing Eucalyptus Oil Has Beneficial Repellent Effect Against Horn Fly (Diptera: Muscidae) - Galli G.M.* (2018)
© The Author(s) 2018. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved.For the first time, the repellent and insecticidal effects of eucalypt essential oil (Eucalyptus globulus) in its free form and associated with different nanostructures (nanoemulsion and nanocapsules) were investigated against Musca domestica (Diptera: Muscidae) and Haemotobia irritans (Diptera: Muscidae) flies. Specimens of M. domestica were collected, separated into groups (n = 10), treated with aspersion of essential oil of eucalypt in its free (1, 5, and 10%) and nanostructured (nanoemulsion or nanoencapsulated at 1, 3, and 5%, respectively) forms. The determination of the insecticidal effect was performed by counting the number of dead flies at intervals of 30, 60, 120, 360 and 750 min after oil aspersion. E. globulus essential oil showed insecticidal effect against M. domestica at concentrations of 1 and 5%. Eucalypt essential oil (10%) caused 100% mortality of M. domestica after 750 min of the treatment. Nanocapsules (3 and 5%) showed efficacy by reducing the number of flies. On the other hand, nanoemulsion did not show insecticidal effect. The repellent action of E. globulus concentrations of 5% was tested against H. irritans on naturally infested cows. The repellent action against H. irritans was verified soon after pulverization. After 24 h, a significant reduction on horn flies' population (83.33 and 66.66%) was observed using free and nanoencapsulated forms tested, respectively. E. globulus essential oil demonstrated insecticidal and repellent effects against M. domestica and H. irritans flies.